(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
يسعى البحث إلى محاولة إجمال خصائص أعمال القصيبي الروائية, وأكثر هذه الخصائص بروزا هي استخدامه للغة الشعرية في أعماله الروائية, على الرغم من الاختلاف القائم بين اللغة الشعرية واللغة النثرية. ولغة القصيبي الشعرية امتازت بصفات أهمها: شعرية الجملة, والتكثيف اللغوي عبر الخيال والصورة النثرية This study tries to summarize the advantages of the prose works of AL- Kussaibi. The most important feature that appears in his works is Poetical language in spite of the difference between the Poetical language and Prosaic language . His Poetical language has the following important points: 1- Poetic sentences 2- Use of words that have many meanings 3- The Pros figures of speech.